Non-tumoral uptake of 68Ga-FAPI-04 PET: A retrospective study - Na Qi; Hao Wang; Haiyan Wang; Shuhua Ren; Zhiwen You; Xing Chen; Yihui Guan; Fang Xie; Fengchun Hua; Jun Zhao (Frontiers in Oncology, 2022)
ObjectiveFibroblast activation protein (FAP)-targeting radiopharmaceutical based on the FAP-specific inhibitor (FAPI) is considered as a potential alternative agent to FDG for tumor-specific imaging. However, FAP is also expressed in normal adult tissues. The aim of this study was to explore the image features of non-tumoral regions with high uptake of 68Ga-FAPI-04 in positron emission tomography (PET) imaging and to reveal the physiological mechanisms of these regions.MaterialA total of 137 patients who underwent whole-body 68Ga-FAPI-04 PET/MR (n=46) or PET/CT (n=91) were included in this retrospective study. Three experienced nuclear medicine physicians determined the non-tumoral regions according to other imaging modalities (CT, MRI, 18F-FDG PET, or ultrasound), clinical information, or pathological results. The regions of interest (ROIs) were drawn manually, and the maximum standardized uptake value (SUVmax) was measured.ResultsA total of 392 non-tumoral uptake regions were included in this study. The included physiological regions were uterus (n=38), submandibular gland (n=118), nipple (n=37), gingiva (n=65), and esophagus (n=31). The incidence of 68Ga-FAPI-04 uptake in physiological regions was independent of age, the tracer uptakes in the gingiva and esophagus were more common in male patients (p=0.006, 0.009), while that in the nipple was more common in female patients (p < 0.001). The included benign regions were inflammatory lymph node (n =10), pneumonia (n=13), atherosclerosis (n=10), pancreatitis (n=18), osteosclerosis (n=45), and surgical scar (n=7). No significant difference was observed in SUVmax between physiological and benign regions.ConclusionsA number of organs exhibit physiological uptakes of 68Ga-FAPI-04. Our study showed that regions with high 68Ga-FAPI-04 uptake did not necessarily represent malignancy. Being familiar with physiological and typical benign 68Ga-FAPI-04 uptake regions can be helpful for physicians to interpret images and to make an accurate diagnosis.